Keanekaragaman Arthropoda tanaman pokem (Setaria italica) menggunakan teknik yellow trap - Nandini Ayuningtias; Syaifullah Rahim; Sari, Nindi; Safitri, Desi Anugra (Universitas Djuanda, 2025)
This study aims to analyze the diversity and functional groups of Arthropods in the pokem (Setaria italica) agroecosystem in Manokwari Regency, West Papua, as an effort to support food security based on local potential. Sampling was carried out using yellow sticky traps installed at 30, 60, and 90 days after planting. The identification of arthropods was carried out at the Pest Laboratory, Faculty of Agriculture, University of Papua. The data were analyzed using the Shannon-Wiener diversity index (H'), the evenness index (E), and the Simpson dominance index (C). The results showed that arthropod diversity was moderate (H' = 2.28) with high evenness (E = 0.66) and low dominance (C = 0.23). A total of 1,701 arthropod individuals were identified, belonging to 9 orders and 31 families, with functional groups including pests, predators, parasitoids, pollinators, and decomposers. The main pests found were Tephritidae (fruit flies) and Cicadellidae (leafhoppers), but the presence of natural enemies such as Coccinellidae (predators) and Mymaridae (parasitoids) was also significant. These conditions indicate a relatively balanced and stable pokem agroecosystem. It was concluded that yellow sticky traps are effective as a monitoring tool, and the diversity of arthropods found can be the basis for developing an ecology-based Integrated Pest Management (IPM) strategy to support sustainable pokem production.